Active scaffold for on-demand drug and cell delivery - Ng, Candy Ting Ting. (2012)
Cancer is a leading cause of death worldwide and side effects on cancer patients from conventional cancer treatment therapy are inevitable. Polymer coated magnetic nanoparticles (MNP) are attractive drug carriers for targeting specific tumors with minimal systemic distribution of the anti-cancer drugs. The objective of this work is to develop and study a polymer-magnetic drug delivery system consisting of iron oxide nanoparticles as the magnetic component and alginate as the polymer.